Islam dan Kearifan Lokal: Dilektika Faham dan Praktik Keagamaan Komunitas Kokoda-Papua dalam Budaya Lokal - Muhammad Rais Amin (STAI ALHIKMAH Jakarta, 2011)
The community of Kokoda is a Muslim community of indigenous Papuans. Their existence in the city of Sorong begins from their migration from Inawatan, one of the hinterlands of West Papua. Islam is a religion of the majority of this community and only a few adherents are Christians. Both adherents are integrated in the same environment. The topic of interest in this study is the dialectic of Islam and the local wisdom that is understood and practiced by this community. In addition, the local wisdom that is practiced by both adherents is out of religious context, even the wisdom which is conceived as “brotherhood” or “sapu sodara” is preserved, maintained and preserved well until it ties emotional connection of Kokoda tribe. This research aims to find the dialectic of Islam and local wisdom in the context of religious understanding of Kokoda community. Therefore, three methods are used for this research namely observation, interview, and thick description. The data is processed by phenomenology analysis technique which is to uncover the social consciousness and collective consciousness of a community. The results of this study show that in fact the practice and religious understanding of the community of Kokoda are from a single concept of “brotherhood” or “sapu sodara”. Their knowledge of religious is based on trust and motivation. Meanwhile their practices are based on: 1) the establishment of committees of religious activities, 2) participation in giving alms, and 3) togetherness in ritual and ceremonial practices. There are two forms of local wisdom of Kokoda community namely: 1) through behavior and 2) refers to the knowledge (cognitive). The dialectic of religion and local wisdom in religious practices of Kokoda also seen in two things: 1) inclusion of religious practices, and 2) inter-religious acculturation. Keywords: Religion (Islam), local wisdom, dialectics, ideology and religious practices, Kokoda. Komunitas Kokoda adalah komunitas muslim yang berasal dari penduduk asli Papua. Eksistensinya di Kota Sorong diawali dengan migrasi dari Inawatan, salah satu daerah pedalaman Papua Barat. Islam merupakan agama mayoritas yang dianut oleh komunitas ini dan hanya sebagian kecil saja penganut Kristiani. Keduanya terintegrasi dalam lingkungan yang sama. Isu yang menarik dalam kajian ini adalah adanya dialektika agama (Islam) dan kearifan lokal yang dipahami dan dipraktikkan oleh komunitas ini. Selain itu, adanya kearifan lokal yang dipraktikkan kedua penganutnya [Islam-Kristen] di luar konteks agama, bahkan kearifan yang dikonsepsikan “persaudaraan” atau “sapu sodara” itu dipelihara, dijaga dan dilestarikan dengan baik hingga mengikat hubungan emosional-kesukuan Kokoda. Riset ini bertujuan mencari dialektika agama [Islam] dan kearifan lokal dalam konteks pemahaman keagamaan komunitas Kokoda. Karenanya, untuk mengupasnya digunakan tiga metode, yaitu observasi, interview, dan thick description. Data tersebut diolah dengan teknik analisis fenomenologi. Analisis ini untuk mengungkap kesadaran sosial dan kesadaran kolektif dari suatu komunitas tersebut. Hasil kajian ini menunjukkan bahwa ternyata praktik dan pemahaman keagamaan komunitas Kokoda bersumber dari konsep tunggal “persaudaraan” atau “sapu sodara”. Pengetahuan keagamaannya dilihat pada unsur kepercayaan dan motivasi. Sedang praktiknya pada; 1) Pembentukan kepanitian kegiatankegiatan keagamaan. 2) Berpartisipasi memberikan sedekah, dan 3) Bersama-sama dalam ritual dan seremonialnya. Ada dua wujud kearifan lokal dari komunitas Kokoda; 1) Lewat Perilaku; 2) Mengacu pada pengetahuan (kognitif). Sedangkan, dialektika agama dan kearifan lokal dalam praktik keagamaan Kokoda juga dilihat dalam dua hal; 1) Inklusifitas praktik keagamaan dan 2) Akulturasi budaya antar agama. Kata Kunci : Agama (Islam), Kearifan Lokal, Dialektika, Faham dan Praktik Keagamaan, Kokoda.